Literature Review the Effect of Wages, Loyalty, Motivation, and Job Satisfaction on Teacher Performance - CHOLID, IDHAM; Sofia Ulfa Eka Hadiyanti (Universitas Muhammadiyah Kalimantan Timur, 2025)
Confronted with teacher shortages and constrained budgets, many developing nations have resorted to lowering certification and education prerequisites, abolishing teacher tenure, and reducing teacher salaries in order to address the gaps in their teaching staff. A review of existing literature demonstrates that these measures have given rise to a parallel group of teachers who are typically inadequately trained, undercompensated, often younger, and inexperienced, employed on local contract terms. While these practices are generally seen as beneficial in terms of improving access, cost-effectiveness, and local accountability, scholar express concerns regarding the long-term sustainability of this approach. They also highlight potential negative consequences for educational equity, specifically in terms of teacher distribution, teacher morale, and the professional standing of the teaching profession. In addition to these factors, there are other factors that are influenced by the teacher performance, namely: wages, loyalty, motivation, and job satisfaction.